Water-permeable concrete for garden road and preparation method of water-permeable concrete

Through the application of modified sepiolite, lignin and high-strength high-mode polyvinyl alcohol fibers, the problems of low permeability coefficient, poor freeze-thaw resistance and poor wear resistance in garden road applications are solved, and high water permeability is achieved , comprehensive improvement of freeze-thaw resistance and wear resistance.

CN119263749AInactive Publication Date: 2025-01-07WEIFANG SANJIANTAI BUILDING MATERIALS CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411805561.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the application of garden roads, existing permeable concrete has low permeability coefficient, poor freeze-thaw resistance and poor wear resistance, making it difficult to meet the requirements of high standards of use.

Method used

Prepare permeable concrete for garden roads using specific formulas and processes, including modified sepiolite reinforcement, modified lignin and modified polyvinyl alcohol fibers, through the cross-linking network of phosphoric acid and ethylenediaminetetraacetic acid, chloroacetic acid The surface carboxylation modification and chemical bonding of high-strength and high-mode polyvinyl alcohol fibers improve the cementing strength and freeze-thaw resistance of concrete.

Benefits of technology

It significantly improves the permeability coefficient, freeze-thaw resistance and wear resistance of water-permeable concrete, meets the high standard use needs of garden roads, and has high compressive strength, low freeze-thaw loss rate and good wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to water-permeable concrete for a garden road and a preparation method thereof, and belongs to the technical field of water-permeable concrete.The water-permeable concrete for the garden road is prepared from 100-250 parts of Portland cement, 300-500 parts of graded aggregate, 8-20 parts of a modified sepiolite reinforcing agent, 10-30 parts of modified lignin, 1-8 parts of modified polyvinyl alcohol fibers, 2-5 parts of a polycarboxylate superplasticizer and 60-100 parts of water; according to the prepared pervious concrete for the garden road, the 28-day compressive strength is 30.1-33.2 MPa, the 28-day breaking strength is 4.8-5.9 MPa, the porosity is 18.9-22.6%, the permeation coefficient is 20.4-22.9 mm / s, the compressive strength loss rate of 100 times of circulation in the aspect of freeze-thaw resistance is 0.9-1.4%, the compressive strength loss rate of 300 times of circulation is 1.5-2.3%, and the mass loss rate of wear resistance is 2.7-4.1%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to permeable concrete for garden roads and a preparation method thereof, belonging to the technical field of permeable concrete. Background Art

[0002] Permeable concrete, also known as porous concrete, refers to concrete with an internal porosity greater than 10%, generally 15-30%, and most pore sizes greater than 1 mm, which has good permeability. Permeable concrete can be used for road structures such as garden roads and residential roads, sidewalks, squares, and parking lots. With people's demand for high greening rates in living environments and high standards for scenic area construction, the application of permeable concrete in urban gardens and scenic area garden roads is becoming more and more extensive, and corresponding permeable concrete has also exposed more and more problems in the use of garden roads. First of all, the water storage rate of garden roads is relatively high, and rainwater is more likely to accumulate, so the permeability requirements for permeable concrete are relatively higher. Secondly, the permeable concrete paved with garden roads is in a relatively humid environment all year round, especially in the winter in the north, the garden roads freeze and thaw many times, which places relatively harsh requirements on the freeze-thaw resistance of permeable concrete. Finally, permeable concrete is a whole formed by cement slurry bonding coarse aggregate. Due to its unique large-void structure and permeable characteristics, the bite force between aggregates is weak, and it is very easy to fall off under external loads, so its wear resistance is generally poor. Therefore, increasing the bonding strength between aggregate particles and improving wear resistance are one of the foundations for the long-term normal service of permeable concrete pavement.

[0003] Chinese patent CN112279575A discloses a highly permeable concrete and a preparation method thereof, wherein the highly permeable concrete comprises the following raw materials by weight: 100-150 parts of cement; 30-60 parts of water; 300-400 parts of coarse aggregate; 5-15 parts of steelmaking slag; 20-50 parts of mesoporous material; 2-10 parts of water reducer; 3-8 parts of reinforcing agent; 0.1-0.4 parts of steel fiber; the mesoporous material comprises at least one of sepiolite, silicon oxide and manganese dioxide; the reinforcing agent is a mixture of titanate coupling agent, alkylphenol polyethylene ether and aluminum oxide. The water permeability coefficient of the highly permeable concrete obtained in the patent can reach up to 20.2 mm / s, which basically meets the use requirements of garden roads, but the patent does not disclose the freeze-thaw resistance and wear resistance of the permeable concrete, and only tests the compressive strength, which is relatively good.

[0004] Chinese patent CN110563429A discloses a high-strength permeable concrete, which includes the following components by weight: 300-400 parts of cement, 1000-1300 parts of modified coarse aggregate, 20-45 parts of admixture, 100-170 parts of mixing water, 3-10 parts of fiber, and 1-10 parts of water reducer; the modification steps of the modified coarse aggregate are: S1: soaking the coarse aggregate in a 10-30% polyvinyl alcohol aqueous solution for 10-20 hours, and then airing the coarse aggregate to semi-dry; S2: sticking silicon powder, polyvinyl alcohol powder and calcium oxide particles on the outside of the semi-dried coarse aggregate, and then further drying the coarse aggregate. The water permeability coefficient of the high-strength permeable concrete obtained in this patent can only reach 7.3mm / s, which is difficult to meet the use of garden roads.

[0005] From the above, it can be seen that the current permeable concrete still has prominent problems such as low permeability coefficient, poor freeze-thaw resistance and poor wear resistance, and is not very suitable for the paving of garden roads. Therefore, the development of permeable concrete with high permeability coefficient, good freeze-thaw resistance and good wear resistance is of great practical significance for its durable use in garden roads. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a permeable concrete for garden roads and a preparation method thereof, so as to achieve the following invention objectives: to prepare permeable concrete for garden roads with high water permeability, good freeze-thaw resistance and good wear resistance.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A permeable concrete for garden roads and a preparation method thereof, wherein the specific formula of the permeable concrete for garden roads is, in parts by weight: 100~250 parts of Portland cement, 300~500 parts of graded aggregate, Modified sepiolite enhancer 8-20 parts, 10~30 parts of modified lignin, Modified polyvinyl alcohol fiber 1~8 parts, 2~5 parts of polycarboxylate water reducer, 60~100 parts of water; The graded aggregate is a mixture of limestone crushed stone meeting the grading standard, and the grading standard is: the percentage passing through the 26.5mm sieve hole is 100wt%, the percentage passing through the 19.0mm sieve hole is 90-98wt%, the percentage passing through the 13.2mm sieve hole is 65-93wt%, the percentage passing through the 9.5mm sieve hole is 20-75wt%, the percentage passing through the 4.75mm sieve hole is 10-25wt%, the percentage passing through the 2.36mm sieve hole is 3-7wt%, the percentage passing through the 1.18mm sieve hole is 1-4wt%, and the percentage passing through the 0.6mm sieve hole is 0wt%; The following are further improvements to the above technical solution: Step 1, preparation of modified sepiolite enhancer After the sepiolite powder is placed in a 90-105°C oven and dried for 7-14 hours, it is added to a high-speed stirring and dispersing kettle, and then deionized water is added, and the stirring rate is controlled to be 4500-6500 rpm, and after strong stirring and dispersion for 4-10 hours, the stirring rate is reduced to 2000-3000 rpm, and then phosphoric acid and ethylenediaminetetraacetic acid are added, and after stirring for 30-60 minutes, the stirring is stopped, and the material is left to stand for 20-30 hours, and the material is filtered, and the filtered solid is placed in a 50-65°C oven and dried for 9-15 hours to obtain a modified sepiolite enhancer; The particle size of the sepiolite powder is 1-100 μm; The mass ratio of the sepiolite powder, deionized water, phosphoric acid and ethylenediaminetetraacetic acid is 50-90:200-350:1-5:10-50.

[0008] Step 2: Preparation of modified lignin After drying the lignin powder at 70-95°C for 10-18 hours, the powder is placed in a high-speed shear dispersion reactor, and then chloroform is added. The shear dispersion rate is controlled at 6000-10000 rpm. After strong shear dispersion for 6-13 hours, the shear dispersion rate is reduced to 2000-3000 rpm. Then, the material in the reactor is heated and kept at a constant temperature of 40-65°C. Under condensation reflux, triethylamine is added, and then chloroacetic acid is added dropwise at a rate of 5-30 g / min. After the addition is completed, the constant temperature dispersion shear reaction is continued for 3-6 hours, and then the temperature is cooled to room temperature. The material is filtered, and the filtered solid is washed 2-4 times with anhydrous ethanol, and naturally dried to obtain modified lignin. The particle size of the lignin powder is 600-1000 mesh; The mass ratio of the lignin powder, chloroform, triethylamine and chloroacetic acid is 60-100:120-250:5-15:15-45.

[0009] Step 3: Preparation of modified polyvinyl alcohol fiber Put high-strength and high-modulus polyvinyl alcohol staple fibers and toluene into a reactor, control the stirring rate at 900-1600 rpm, raise the temperature in the reactor and keep the temperature constant at 65-85°C, add triethylamine under condensation reflux, and then drop nitrogen-containing formyl chloride into the reactor at a rate of 0.5-30 g / min. After the dropwise addition is completed, continue to react at a constant temperature for 4-8 hours, cool to room temperature, discharge and filter, wash the filtered high-strength and high-modulus polyvinyl alcohol staple fibers with anhydrous ethanol for 2-4 times, and dry naturally to obtain surface chlorinated high-strength and high-modulus polyvinyl alcohol staple fibers, then put the surface chlorinated high-strength and high-modulus polyvinyl alcohol staple fibers into a reactor, add water glass solution into the reactor, control the stirring rate at 400-1000 rpm, raise the temperature and keep the temperature constant at 50-80°C, stir and react at a constant temperature for 5-9 hours, cool to room temperature, discharge and filter, wash the filtered fibers with deionized water for 2-3 times, and then dry naturally to obtain modified polyvinyl alcohol fibers; The nitrogen-containing formyl chloride is one of methylaminoformyl chloride and N-methylaminoformyl chloride; The high-strength and high-modulus polyvinyl alcohol short fibers have a diameter of 8 to 14 μm, a length of 3 to 8 mm, a tensile strength of 1300 to 1550 MPa, a Young's modulus of 35 to 40 GPa, and an elongation at break of 5 to 9%; The mass ratio of the high-strength and high-modulus polyvinyl alcohol staple fibers, toluene, triethylamine, and nitrogen-containing carbonyl chloride is 25-65:120-350:3-9:8-20; The water glass solution is one of a sodium metasilicate aqueous solution and a potassium silicate aqueous solution; The water glass solution has a mass concentration of 10-35wt% and a modulus of 1.5-3.5; The mass ratio of the surface chlorinated high-strength and high-modulus polyvinyl alcohol short fibers to the water glass solution is 1-7:13.

[0010] Step 4: Preparation of permeable concrete for garden roads According to the specific formula of permeable concrete for garden roads in parts by weight, first put water, polycarboxylic acid water-reducing agent, modified polyvinyl alcohol fiber, modified lignin, and modified sepiolite reinforcing agent into a mixer, stir for 15 to 30 minutes, then add silicate cement, continue stirring for 6 to 15 minutes, then add graded aggregate, continue stirring for 1 to 3 minutes, and then discharge the material to obtain permeable concrete for garden roads that can be directly used for paving.

[0011] Compared with the prior art, the present invention achieves the following beneficial effects: 1. The present invention utilizes the strong adsorption of sepiolite. Under the dissolution promoting effect of phosphoric acid, ethylenediaminetetraacetic acid is adsorbed into the internal micropores of sepiolite. When the sepiolite adsorbed with ethylenediaminetetraacetic acid is added into the permeable concrete, the sepiolite will be enriched to a certain extent on the surface of aggregate gravel due to its strong adsorption performance. In this way, the sepiolite establishes a transition layer between the surface of silicate cement and the aggregate gravel. Moreover, when the transition layer is established, the heat released by the hydration exothermic reaction during the curing process of silicate cement will cause the ethylenediaminetetraacetic acid adsorbed in the internal micropores of the sepiolite to gradually overflow and wrap around the outer surface of the sepiolite. The ethylenediaminetetraacetic acid can easily complex the calcium ions in the silicate cement. Calcium ions are the main ions of the hydration reaction. The key active ions that occur are the active centers of cement curing reactions. This will establish a cross-linked cement curing network with the EDTA-complexed calcium ions on the outer surface of sepiolite as the center. The sepiolite is located at the center of this cross-linked curing network. Therefore, the sepiolite adsorbed with EDTA will establish a reaction center point of a cement curing cross-linked network on the surface of aggregate gravel. A large number of cross-linked network reaction centers composed of numerous sepiolites cover the surface of aggregate gravel. In this way, a strong chemical adsorption bonding layer with a sepiolite transition layer as the basic morphological feature is formed between the silicate cement and the aggregate gravel surface. The cementing structure constructed in this way can effectively improve the mechanical properties, freeze-thaw resistance and wear resistance of permeable concrete. 2. The present invention uses chloroacetic acid to modify the surface of lignin powder by carboxylation. The compatibility of the modified lignin powder with silicate cement is improved to a certain extent. Moreover, the surface of the modified lignin powder is covered with carboxyl hydroxyl groups, which is similar to the molecular structure of polycarboxylic acid water reducer. In the formula of permeable concrete, the surface carboxyl-modified lignin has a considerable function of a water reducer, which can reduce the collapse of silicate cement during curing, increase the density of silicate cement after curing, and thus improve its compressive strength. In addition, compared with the hard silicate cement solid, lignin itself has a certain flexibility. After adding lignin powder, the low-temperature hardness and brittleness of silicate cement solid can be improved to a certain extent, so that the freeze-thaw resistance of silicate cement solidification itself is improved to a certain extent. 3. The present invention first uses methylaminoformyl chloride or N-methylaminoformyl chloride to react with the alcohol hydroxyl group on the surface of the high-strength and high-modulus polyvinyl alcohol fiber, and replaces the alcohol hydroxyl group on the end of the surface of the high-strength and high-modulus polyvinyl alcohol fiber with a primary amine group or a secondary amine group, and the primary amine group or the secondary amine group then reacts with sodium water glass or potassium water glass to generate sodium silanamide or potassium silanamide. Sodium silanamide or potassium silanamide has certain inorganic salt properties. After these two salts are chemically bonded to the surface of the high-strength and high-modulus polyvinyl alcohol fiber, they can participate in the hydration reaction of silicate cement after being subsequently added to the permeable concrete, and further react with the alkaline substances in the silicate cement. In this way, the high-strength and high-modulus polyvinyl alcohol fiber The polyvinyl alcohol fiber reacts chemically with silicate cement through the sodium silanamide or potassium silanamide chemically bonded on the surface. The mixing reinforcement mode of the high-strength and high-modulus polyvinyl alcohol fiber on the permeable concrete changes from simple physical mixing reinforcement to a composite of physical mixing reinforcement and chemical bonding reinforcement. Therefore, the modified polyvinyl alcohol fiber prepared in the present invention, on the basis of effectively utilizing the high strength and high modulus characteristics of the high-strength and high modulus polyvinyl alcohol fiber itself, eliminates the interface effect of physical reinforcement through an innovative chemical bonding method, and maximizes the reinforcement and toughening effect of the high-strength and high modulus polyvinyl alcohol fiber. 4. The permeable concrete for garden roads prepared by the present invention has a 28-day compressive strength of 30.1-33.2 MPa, a 28-day flexural strength of 4.8-5.9 MPa, a porosity of 18.9-22.6%, a water permeability of 20.4-22.9 mm / s, and an anti-freezing and thawing performance. The loss rate of compressive strength after 100 cycles is 0.9-1.4%, the loss rate of compressive strength after 300 cycles is 1.5-2.3%, and the mass loss rate of wear resistance is 2.7-4.1%. DETAILED DESCRIPTION

[0012] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0013] Example 1: A method for preparing permeable concrete for garden roads Step 1, preparation of modified sepiolite enhancer After the sepiolite powder was placed in an oven at 100° C. and dried for 11 hours, it was added to a high-speed stirring and dispersing kettle, and then deionized water was added. After the stirring rate was controlled at 6000 rpm and the mixture was vigorously stirred and dispersed for 8 hours, the stirring rate was reduced to 2600 rpm, phosphoric acid and ethylenediaminetetraacetic acid were then added, and the mixture was stirred for 50 minutes, and then the stirring was stopped. After the mixture was allowed to stand for 26 hours, the material was filtered, and the filtered solid was placed in an oven at 60° C. and dried for 11 hours to obtain a modified sepiolite reinforcing agent. The particle size of the sepiolite powder is 30 μm; The mass ratio of the sepiolite powder, deionized water, phosphoric acid and ethylenediaminetetraacetic acid is 60:300:4:40.

[0014] Step 2: Preparation of modified lignin After drying the lignin powder at 80°C for 13 hours, the powder was placed in a high-speed shear dispersion reactor, and then chloroform was added. The shear dispersion rate was controlled at 8500 rpm. After strong shear dispersion for 11 hours, the shear dispersion rate was reduced to 2600 rpm. Then, the material in the reactor was heated and kept at a constant temperature of 50°C. Under the condensation reflux state, triethylamine was added, and then chloroacetic acid was added dropwise at a rate of 20 g / min. After the addition was completed, the constant temperature dispersion shear reaction was continued for 5 hours, and then the temperature was cooled to room temperature. The material was filtered, and the filtered solid was washed with anhydrous ethanol for 3 times, and the modified lignin was obtained after natural drying. The particle size of the lignin powder is 900 mesh; The mass ratio of the lignin powder, chloroform, triethylamine and chloroacetic acid is 90:220:11:30.

[0015] Step 3: Preparation of modified polyvinyl alcohol fiber Put high-strength and high-modulus polyvinyl alcohol staple fibers and toluene into a reactor, control the stirring rate at 1100 rpm, raise the temperature in the reactor and keep the temperature constant at 80°C, add triethylamine under condensation reflux, and then drop nitrogen-containing formyl chloride into the reactor at a rate of 6 g / min. After the dropwise addition is completed, continue to react at a constant temperature for 7 hours, cool to room temperature, discharge and filter, wash the filtered high-strength and high-modulus polyvinyl alcohol staple fibers with anhydrous ethanol for 3 times, and dry naturally to obtain surface chlorinated high-strength and high-modulus polyvinyl alcohol staple fibers, then put the surface chlorinated high-strength and high-modulus polyvinyl alcohol staple fibers into a reactor, add water glass solution into the reactor, control the stirring rate at 800 rpm, raise the temperature and keep the temperature constant at 70°C, stir and react at a constant temperature for 6 hours, cool to room temperature, discharge and filter, wash the filtered fibers with deionized water for 2 times, and then dry naturally to obtain modified polyvinyl alcohol fibers; The nitrogen-containing formyl chloride is methylaminoformyl chloride; The high-strength and high-modulus polyvinyl alcohol short fibers have a diameter of 10 μm, a length of 5 mm, a tensile strength of 1450 MPa, a Young's modulus of 38 GPa, and an elongation at break of 6%; The mass ratio of the high-strength and high-modulus polyvinyl alcohol staple fibers, toluene, triethylamine, and nitrogen-containing carbonyl chloride is 40:250:7:15; The water glass solution is a sodium metasilicate aqueous solution; The water glass solution has a mass concentration of 25 wt % and a modulus of 2. The mass ratio of the surface chlorinated high-strength and high-modulus polyvinyl alcohol short fibers to the water glass solution is 5:13.

[0016] Step 4: Preparation of permeable concrete for garden roads The specific formula of the permeable concrete for garden roads is, in parts by weight: 200 parts of Portland cement, 450 parts of graded aggregate, 14 parts of modified sepiolite enhancer, 13 parts of modified lignin, 3 parts of modified polyvinyl alcohol fiber, 4 parts of polycarboxylate water reducer, 80 parts water; The graded aggregate is a mixture of limestone crushed stone meeting the grading standard, wherein the grading standard is: the percentage passing through a 26.5 mm sieve hole is 100 wt%, the percentage passing through a 19.0 mm sieve hole is 95 wt%, the percentage passing through a 13.2 mm sieve hole is 80 wt%, the percentage passing through a 9.5 mm sieve hole is 65 wt%, the percentage passing through a 4.75 mm sieve hole is 15 wt%, the percentage passing through a 2.36 mm sieve hole is 4 wt%, the percentage passing through a 1.18 mm sieve hole is 2 wt%, and the percentage passing through a 0.6 mm sieve hole is 0 wt%; According to the specific formula of permeable concrete for garden roads in parts by weight, first put water, polycarboxylic acid water-reducing agent, modified polyvinyl alcohol fiber, modified lignin, and modified sepiolite reinforcing agent into a mixer, stir for 20 minutes, then add silicate cement, continue stirring for 10 minutes, then add graded aggregate, continue stirring for 2 minutes, and then discharge the material to obtain permeable concrete for garden roads that can be directly used for paving.

[0017] Example 2: A method for preparing permeable concrete for garden roads Step 1, preparation of modified sepiolite enhancer After the sepiolite powder was placed in a 90°C oven and dried for 7 hours, it was added to a high-speed stirring and dispersing kettle, and then deionized water was added. After the stirring rate was controlled at 4500 rpm and the dispersion was vigorously stirred for 4 hours, the stirring rate was reduced to 2000 rpm, phosphoric acid and ethylenediaminetetraacetic acid were then added, and the stirring was stopped after stirring for 30 minutes. After the stirring was allowed to stand for 20 hours, the material was filtered, and the filtered solid was placed in a 50°C oven and dried for 9 hours to obtain a modified sepiolite reinforcing agent; The particle size of the sepiolite powder is 1 μm; The mass ratio of the sepiolite powder, deionized water, phosphoric acid and ethylenediaminetetraacetic acid is 50:200:1:10.

[0018] Step 2: Preparation of modified lignin After drying the lignin powder at 70°C for 10 hours, the powder was placed in a high-speed shear dispersion reactor, and then chloroform was added. The shear dispersion rate was controlled at 6000 rpm. After 6 hours of strong shear dispersion, the shear dispersion rate was reduced to 2000 rpm. Then, the material in the reactor was heated and kept at a constant temperature of 40°C. Under the condensation reflux state, triethylamine was added, and then chloroacetic acid was added dropwise at a rate of 5 g / min. After the addition was completed, the constant temperature dispersion shear reaction was continued for 3 hours, and then the temperature was cooled to room temperature. The material was filtered, and the filtered solid was washed twice with anhydrous ethanol, and naturally dried to obtain modified lignin. The particle size of the lignin powder is 600 mesh; The mass ratio of the lignin powder, chloroform, triethylamine and chloroacetic acid is 60:120:5:15.

[0019] Step 3: Preparation of modified polyvinyl alcohol fiber Put high-strength and high-modulus polyvinyl alcohol staple fibers and toluene into a reactor, control the stirring rate at 900 rpm, raise the temperature in the reactor and keep the temperature constant at 65°C, add triethylamine under condensation reflux, and then drop nitrogen-containing formyl chloride into the reactor at a rate of 0.5 g / min. After the dropwise addition is completed, continue to react at a constant temperature for 4 hours, cool to room temperature, discharge and filter, wash the filtered high-strength and high-modulus polyvinyl alcohol staple fibers with anhydrous ethanol twice, and dry them naturally to obtain surface chlorinated high-strength and high-modulus polyvinyl alcohol staple fibers, then put the surface chlorinated high-strength and high-modulus polyvinyl alcohol staple fibers into a reactor, add water glass solution into the reactor, control the stirring rate at 400 rpm, raise the temperature and keep the temperature constant at 50°C, stir and react at a constant temperature for 5 hours, cool to room temperature, discharge and filter, wash the filtered fibers with deionized water twice, and then dry them naturally to obtain modified polyvinyl alcohol fibers; The nitrogen-containing formyl chloride is N-methylcarbamoyl chloride; The high-strength and high-modulus polyvinyl alcohol short fibers have a diameter of 8 μm, a length of 3 mm, a tensile strength of 1300 MPa, a Young's modulus of 35 GPa, and an elongation at break of 5%; The mass ratio of the high-strength and high-modulus polyvinyl alcohol staple fibers, toluene, triethylamine, and nitrogen-containing carbonyl chloride is 25:120:3:8; The water glass solution is a potassium silicate aqueous solution; The water glass solution has a mass concentration of 10 wt % and a modulus of 1.5. The mass ratio of the surface chlorinated high-strength and high-modulus polyvinyl alcohol short fibers to the water glass solution is 1:13.

[0020] Step 4: Preparation of permeable concrete for garden roads The specific formula of the permeable concrete for garden roads is, in parts by weight: 100 parts of Portland cement, 300 parts of graded aggregate, 8 parts of modified sepiolite enhancer, 10 parts of modified lignin, 1 part of modified polyvinyl alcohol fiber, 2 parts of polycarboxylate water reducer, 60 parts of water; The graded aggregate is a mixture of limestone crushed stone meeting the grading standard, and the grading standard is: the percentage passing through the 26.5mm sieve hole is 100wt%, the percentage passing through the 19.0mm sieve hole is 90wt%, the percentage passing through the 13.2mm sieve hole is 65wt%, the percentage passing through the 9.5mm sieve hole is 20wt%, the percentage passing through the 4.75mm sieve hole is 10wt%, the percentage passing through the 2.36mm sieve hole is 3wt%, the percentage passing through the 1.18mm sieve hole is 1wt%, and the percentage passing through the 0.6mm sieve hole is 0wt%; According to the specific formula of permeable concrete for garden roads in parts by weight, first put water, polycarboxylic acid water-reducing agent, modified polyvinyl alcohol fiber, modified lignin, and modified sepiolite reinforcing agent into a mixer, stir for 15 minutes, then add silicate cement, continue stirring for 6 minutes, then add graded aggregate, continue stirring for 1 minute, and then discharge the material to obtain permeable concrete for garden roads that can be directly used for paving.

[0021] Example 3: A method for preparing permeable concrete for garden roads Step 1, preparation of modified sepiolite enhancer After the sepiolite powder was placed in an oven at 105°C and dried for 14 hours, it was added to a high-speed stirring and dispersing kettle, and then deionized water was added. After the stirring rate was controlled at 6500 rpm and the dispersion was vigorously stirred for 10 hours, the stirring rate was reduced to 3000 rpm, phosphoric acid and ethylenediaminetetraacetic acid were then added, and the stirring was stopped after 60 minutes of stirring. After standing for 30 hours, the material was filtered, and the filtered solid was placed in an oven at 65°C and dried for 15 hours to obtain a modified sepiolite reinforcing agent; The particle size of the sepiolite powder is 100 μm; The mass ratio of the sepiolite powder, deionized water, phosphoric acid and ethylenediaminetetraacetic acid is 90:350:5:50.

[0022] Step 2: Preparation of modified lignin After drying the lignin powder at 95°C for 18 hours, the powder was placed in a high-speed shear dispersion reactor, and then chloroform was added. The shear dispersion rate was controlled at 10,000 rpm. After strong shear dispersion for 13 hours, the shear dispersion rate was reduced to 3,000 rpm. The material in the reactor was heated and kept at a constant temperature of 65°C. Under condensation reflux, triethylamine was added, and then chloroacetic acid was added dropwise at a rate of 30 g / min. After the addition was completed, the constant temperature dispersion shear reaction was continued for 6 hours, and then the temperature was cooled to room temperature. The material was filtered, and the filtered solid was washed 4 times with anhydrous ethanol and dried naturally to obtain modified lignin. The particle size of the lignin powder is 1000 mesh; The mass ratio of the lignin powder, chloroform, triethylamine and chloroacetic acid is 100:250:15:45.

[0023] Step 3: Preparation of modified polyvinyl alcohol fiber Put high-strength and high-modulus polyvinyl alcohol staple fibers and toluene into a reactor, control the stirring rate at 1600 rpm, raise the temperature in the reactor and keep the temperature constant at 85°C, add triethylamine under condensation reflux, and then drop nitrogen-containing formyl chloride into the reactor at a rate of 30 g / min. After the dropwise addition is completed, continue to react at a constant temperature for 8 hours, cool to room temperature, discharge and filter, wash the filtered high-strength and high-modulus polyvinyl alcohol staple fibers with anhydrous ethanol for 4 times, and dry naturally to obtain surface chlorinated high-strength and high-modulus polyvinyl alcohol staple fibers, then put the surface chlorinated high-strength and high-modulus polyvinyl alcohol staple fibers into a reactor, add water glass solution into the reactor, control the stirring rate at 1000 rpm, raise the temperature and keep the temperature constant at 80°C, stir and react at a constant temperature for 9 hours, cool to room temperature, discharge and filter, wash the filtered fibers with deionized water for 3 times, and then dry naturally to obtain modified polyvinyl alcohol fibers; The nitrogen-containing formyl chloride is N-methylcarbamoyl chloride; The high-strength and high-modulus polyvinyl alcohol short fibers have a diameter of 14 μm, a length of 8 mm, a tensile strength of 1550 MPa, a Young's modulus of 40 GPa, and an elongation at break of 9%; The mass ratio of the high-strength and high-modulus polyvinyl alcohol staple fibers, toluene, triethylamine, and nitrogen-containing carbonyl chloride is 65:350:9:20; The water glass solution is a sodium metasilicate aqueous solution; The water glass solution has a mass concentration of 35 wt % and a modulus of 3.5. The mass ratio of the surface chlorinated high-strength and high-modulus polyvinyl alcohol short fibers to the water glass solution is 7:13.

[0024] Step 4: Preparation of permeable concrete for garden roads The specific formula of the permeable concrete for garden roads is, in parts by weight: 250 parts of Portland cement, 500 parts of graded aggregate, 20 parts of modified sepiolite enhancer, 30 parts of modified lignin, 8 parts of modified polyvinyl alcohol fiber, 5 parts of polycarboxylate water reducer, 100 parts water; The graded aggregate is a mixture of limestone crushed stone meeting the grading standard, and the grading standard is: the percentage passing through the 26.5mm sieve hole is 100wt%, the percentage passing through the 19.0mm sieve hole is 98wt%, the percentage passing through the 13.2mm sieve hole is 93wt%, the percentage passing through the 9.5mm sieve hole is 75wt%, the percentage passing through the 4.75mm sieve hole is 25wt%, the percentage passing through the 2.36mm sieve hole is 7wt%, the percentage passing through the 1.18mm sieve hole is 4wt%, and the percentage passing through the 0.6mm sieve hole is 0wt%; According to the specific formula of permeable concrete for garden roads in parts by weight, first put water, polycarboxylic acid water-reducing agent, modified polyvinyl alcohol fiber, modified lignin, and modified sepiolite reinforcing agent into a mixer, stir for 30 minutes, then add silicate cement, continue stirring for 15 minutes, then add graded aggregate, continue stirring for 3 minutes, and then discharge the material to obtain permeable concrete for garden roads that can be directly used for paving.

[0025] Comparative Example 1: Based on Example 1, step 1, preparation of modified sepiolite reinforcing agent, is not performed. In step 4, preparation of permeable concrete for garden roads, 14 parts of modified sepiolite reinforcing agent are replaced by 14 parts of sepiolite powder in equal amounts. The specific operation is as follows: Step 1, preparation of modified sepiolite reinforcing agent is not performed; The operations of steps 2 and 3 are the same as those of Example 1; Step 4: Preparation of permeable concrete for garden roads 14 parts of modified sepiolite reinforcing agent were replaced by 14 parts of sepiolite powder, and other operations were the same as in Example 1; The particle size of the sepiolite powder is 30 μm.

[0026] Comparative Example 2: Based on Example 1, step 2, preparation of modified lignin, was not performed. In step 4, preparation of permeable concrete for garden roads, modified lignin was not added, and unmodified lignin was directly added. 13 parts of modified lignin were replaced by 13 parts of lignin powder. The specific operation was as follows: The operation of step 1 is the same as that of embodiment 1; Step 2, preparation of modified lignin, is not performed; The operation of step 3 is the same as that of embodiment 1; Step 4: Preparation of permeable concrete for garden roads The 13 parts of modified lignin were replaced by 13 parts of lignin powder, and the other operations were the same as in Example 1; The particle size of the lignin powder is 900 meshes.

[0027] Comparative Example 3: Based on Example 1, step 3, preparation of modified polyvinyl alcohol fiber, is not performed. In step 4, preparation of permeable concrete for garden roads, 3 parts of modified polyvinyl alcohol fiber are replaced by 3 parts of high-strength and high-modulus polyvinyl alcohol short fibers. The specific operation is as follows: The operations of steps 1 and 2 are the same as those of Example 1; Step 3, preparation of modified polyvinyl alcohol fiber is not performed; Step 4: Preparation of permeable concrete for garden roads The modified polyvinyl alcohol fibers were replaced by 3 parts of high-strength and high-modulus polyvinyl alcohol short fibers in equal amounts, and the other operations were the same as in Example 1; The high-strength and high-modulus polyvinyl alcohol short fibers have a diameter of 10 μm, a length of 5 mm, a tensile strength of 1450 MPa, a Young's modulus of 38 GPa, and an elongation at break of 6%.

[0028] Performance Test: The following indicators were tested on the permeable concrete for garden roads obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3: 1. Compressive strength: According to the national standard "GB / T 50081-2016 Mechanical properties of ordinary concrete Prepare specimens and test compressive strength according to the method specified in the Test Method Standard; 2. Flexural strength: According to the national standard "GB / T 50081-2016 Mechanical properties of ordinary concrete Prepare the specimens and test the flexural strength according to the method specified in the "Test Method Standard"; 3. Porosity: Porosity test of hardened permeable concrete as specified in ASTM C1754 Test method: The porosity of the specimens was measured after 28 days of curing. 4. Water permeability coefficient: According to "CJJ / T 135-2009 Technical Specifications for Permeable Cement Concrete Pavement" The constant head test method in the "Procedure" is tested when the specimen is cured for 28 days; 5. Freeze-thaw resistance: According to GB / T50082-2009 Long-term performance and The test specimens were made according to the requirements of the test specimen molding method in the "Durability Performance Test Method". The size of the molded test specimens was 100mm×100mm×400mm. After curing in a standard curing room for 28 days, they were taken out and immersed in water at (20±2)℃ for 4 days. The water on the surface of the test specimens should be wiped clean after they were taken out. A KDS-60 quick freezing test machine was used. The water level in the chassis was 5mm higher than the test specimen. The system automatically controlled the refrigeration and heating cycles. One cycle lasted 4 hours. The highest temperature was (20±1)℃ and the lowest temperature was (-5±1)℃. Freeze-thaw cycles were performed 100 times and 300 times, and then the compressive strength was tested after 100 times and 300 times of freeze-thaw cycles. The anti-freeze-thaw performance was characterized by the compressive strength loss rate. 6. Wear resistance: Wear resistance test is carried out according to the method specified in ASTM C1747 / C1747M standard, and the quality loss rate is used to characterize the quality of wear resistance; The test results of the above indicators are shown in Table 1: Table 1

[0029] It can be seen from the data in Table 1 that the compressive strength of Examples 1-3 is all above 30 MPa, the flexural strength is also above 4.8 MPa, the porosity is 18.9-22.6%, the water permeability is relatively high, all greater than 20 mm / s, the compressive strength loss rate after 100 and 300 freeze-thaw cycles is all below 2.3%, and the wear resistance index quality loss rate does not exceed 5%, which shows that the permeable concrete for garden roads obtained by the present invention has the advantages of high water permeability, good freeze-thaw resistance and good wear resistance; the sepiolite powder in Comparative Example 1 is not modified, and the The compressive strength and flexural strength decreased significantly, the porosity and permeability coefficient increased slightly, but the freeze-thaw resistance decreased significantly, and the wear resistance also decreased significantly. This shows that after the modification of sepiolite powder, the mechanical properties of permeable concrete are very positively improved, especially the freeze-thaw resistance and wear resistance. This may be because after the modification of sepiolite, it can better promote the adhesion between the silicate cement binder and the aggregate gravel, thereby improving the freeze-thaw resistance and wear resistance. The lignin powder added in Example 2 is not modified, and the compressive strength of Example 2 is The compressive strength and flexural strength of the concrete dropped sharply, the porosity and water permeability increased significantly, and the freeze-thaw resistance and wear resistance also decreased significantly. This may be because if the lignin powder is not modified, the dispersion uniformity is poor, and its water absorption is relatively high, which makes it easier to form local wet agglomeration in the solidified concrete, affecting the freeze-thaw resistance. It may also affect the adhesion between the silicate cement binder and the aggregate, thereby causing a significant decrease in wear resistance. The high-strength and high-modulus polyvinyl alcohol short fibers added in Comparative Example 3 are not surface modified, and the compressive strength and flexural strength of Comparative Example 3 are significantly reduced, the porosity and water permeability coefficient are greatly increased, and the freeze-thaw resistance and wear resistance are also greatly reduced. This may be because if the lignin powder is not modified, the dispersion uniformity is poor, and its water absorption is relatively high, which makes it easier to form local wet agglomeration in the solidified concrete, affecting the freeze-thaw resistance. It may also affect the adhesion between the silicate cement binder and the aggregate, thereby causing a significant decrease in wear resistance. The rate and permeability coefficient have basically not changed, but the freeze-thaw resistance and wear resistance have decreased significantly, especially the wear resistance has decreased significantly. This shows that after surface modification, the high-strength and high-modulus polyvinyl alcohol short fibers can more effectively improve the mechanical properties and freeze-thaw resistance of permeable concrete, especially the improvement of wear resistance. This may be because the surface-modified polyvinyl alcohol fibers have established a stronger chemical adsorption or chemical bonding with the silicate cement and aggregate surface, thereby greatly improving the freeze-thaw resistance and wear resistance of permeable concrete.

[0030] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A permeable concrete for garden roads, characterized in that: The specific formula of the permeable concrete for garden roads is, in parts by weight: 100~250 parts of Portland cement, 300~500 parts of graded aggregate, Modified sepiolite enhancer 8-20 parts, 10~30 parts of modified lignin, Modified polyvinyl alcohol fiber 1~8 parts, 2~5 parts of polycarboxylate water reducer, 60~100 parts of water; The graded aggregate is a mixture of limestone crushed stone meeting the grading standard, and the grading standard is: the percentage passing through the 26.5mm sieve hole is 100wt%, the percentage passing through the 19.0mm sieve hole is 90-98wt%, the percentage passing through the 13.2mm sieve hole is 65-93wt%, the percentage passing through the 9.5mm sieve hole is 20-75wt%, the percentage passing through the 4.75mm sieve hole is 10-25wt%, the percentage passing through the 2.36mm sieve hole is 3-7wt%, the percentage passing through the 1.18mm sieve hole is 1-4wt%, and the percentage passing through the 0.6mm sieve hole is 0wt%; The modified sepiolite enhancer has a preparation method comprising: placing sepiolite powder in an oven at 90-105°C and drying it for 7-14 hours, adding it to a high-speed stirring and dispersing kettle, then adding deionized water, controlling the stirring rate at 4500-6500 rpm, vigorously stirring and dispersing for 4-10 hours, reducing the stirring rate to 2000-3000 rpm, then adding phosphoric acid and ethylenediaminetetraacetic acid, stirring for 30-60 minutes, stopping stirring, standing for 20-30 hours, filtering the material, placing the filtered solid in an oven at 50-65°C and drying it for 9-15 hours, and obtaining the modified sepiolite enhancer; The particle size of the sepiolite powder is 1-100 μm; The modified lignin has a preparation method comprising: drying lignin powder at 70-95°C for 10-18 hours, placing the powder in a high-speed shear dispersion reactor, adding chloroform, controlling the shear dispersion rate at 6000-10000 rpm, and performing strong shear dispersion for 6-13 hours, reducing the shear dispersion rate to 2000-3000 rpm, heating the material in the reactor and keeping the temperature constant at 40-65°C, adding triethylamine under condensation reflux, and then dripping chloroacetic acid at a rate of 5-30 g / min, continuing the constant temperature dispersion shear reaction for 3-6 hours after the dripping is completed, cooling the mixture to room temperature, filtering the discharged material, washing the filtered solid with anhydrous ethanol for 2-4 times, and drying the mixture naturally to obtain the modified lignin; The particle size of the lignin powder is 600-1000 mesh; The modified polyvinyl alcohol fiber is prepared by: placing high-strength and high-modulus polyvinyl alcohol short fibers and toluene in a reaction kettle, controlling the stirring rate to 900-1600 rpm, raising the temperature in the kettle and keeping the temperature constant at 65-85°C, adding triethylamine under condensation reflux, and then dropping nitrogen-containing acetyl chloride into the kettle at a rate of 0.5-30 g / min, continuing the constant temperature reaction for 4-8 hours after the dropwise addition, cooling to room temperature, discharging and filtering, and filtering the filtered high-strength and high-modulus polyvinyl alcohol short fibers with anhydrous After washing with ethanol for 2 to 4 times, the mixture is naturally dried to obtain high-strength and high-modulus polyvinyl alcohol short fibers with surface chlorination, and then the high-strength and high-modulus polyvinyl alcohol short fibers with surface chlorination are put into a reaction kettle, and then a water glass solution is added into the kettle, and the stirring rate is controlled at 400 to 1000 rpm, and the temperature is raised and kept constant at 50 to 80° C. After constant temperature stirring and reaction for 5 to 9 hours, the temperature is lowered to room temperature, the material is discharged and filtered, and the filtered fibers are washed with deionized water for 2 to 3 times, and then naturally dried to obtain modified polyvinyl alcohol fibers; The nitrogen-containing formyl chloride is one of methylaminoformyl chloride and N-methylaminoformyl chloride; The high-strength and high-modulus polyvinyl alcohol short fibers have a diameter of 8 to 14 μm, a length of 3 to 8 mm, a tensile strength of 1300 to 1550 MPa, a Young's modulus of 35 to 40 GPa, and an elongation at break of 5 to 9%; The water glass solution is one of a sodium metasilicate aqueous solution and a potassium silicate aqueous solution; The water glass solution has a water glass mass concentration of 10-35wt% and a water glass modulus of 1.5-3.

5.

2. The permeable concrete for garden roads according to claim 1 is characterized in that: The mass ratio of the sepiolite powder, deionized water, phosphoric acid and ethylenediaminetetraacetic acid is 50-90:200-350:1-5:10-50.

3. The permeable concrete for garden roads according to claim 1, characterized in that: The mass ratio of the lignin powder, chloroform, triethylamine and chloroacetic acid is 60-100:120-250:5-15:15-45.

4. The permeable concrete for garden roads according to claim 1, characterized in that: The mass ratio of the high-strength and high-modulus polyvinyl alcohol staple fibers, toluene, triethylamine, and nitrogen-containing carbonyl chloride is 25-65:120-350:3-9:8-20; The mass ratio of the surface chlorinated high-strength and high-modulus polyvinyl alcohol short fibers to the water glass solution is 1-7:

13.

5. The method for preparing permeable concrete for garden roads according to claim 1, characterized in that: The preparation method of the permeable concrete for garden roads is as follows: according to the specific formula of the permeable concrete for garden roads in parts by weight, water, polycarboxylic acid water-reducing agent, modified polyvinyl alcohol fiber, modified lignin, and modified sepiolite reinforcing agent are first put into a mixer, stirred for 15 to 30 minutes, and then silicate cement is added, and the stirring is continued for 6 to 15 minutes, and then the graded aggregate is added, and the stirring is continued for 1 to 3 minutes, and the permeable concrete for garden roads that can be directly used for paving is obtained by discharging the material.

Citation Information

Patent Citations

  • High-strength pervious concrete

    CN110563429A

  • High-permeability concrete and preparation method thereof

    CN112279575A

  • Sand-free pervious concrete

    CN108546052A

  • CF50 concrete and preparation process thereof

    CN112521065A

  • Modified lignin self-repairing conductive hydrogel as well as preparation method and application thereof

    CN114656654A